Influence of Full-Life Cycle Wheel Profile on the Contact Performance of Wheel and Standard Fixed Frog in Heavy Haul Railway - He Ma; Jinming Zhang; Jun Zhang; Tao Tao Jin; Chun Yu Song (Shock and Vibration)
Wheel wear is unavoidable, which affects the contact performance of the wheel and rail. This article explores the effects of wheel profile wear on the static contact and dynamic interaction between wheel and standard fixed frog in heavy haul railway. The coupling dynamic models of the vehicle-fixed frog system are established to calculate the change regulation of displacement, contact force, and acceleration when a vehicle passes through the standard fixed frog at a speed of 50 km/h in the facing move in the diverging line. Besides, the finite element models of wheel and standard fixed frog at key positions are developed to simulate the contact patch and distribution of von Mises stress in the regions of the wheel-fixed frog. Compared with the standard profile, the maximum lateral displacement of the worn profile can be reduced by up to 9 mm. The vertical contact force can be reduced from 750 kN to 320 kN, and the decrease is 57.3%. The von Mises stress could decrease up to 34% compared with the standard. And the results show that the wheel profile wear changes the positions of the wheel-rail contact points along the longitudinal direction and affects the dynamic interaction of vehicle and standard fixed frog. For the measured worn wheel profiles in this article, profile wear relieves the dynamic responses and it is good for the nose rail.